2020
DOI: 10.1002/ijch.202000092
|View full text |Cite
|
Sign up to set email alerts
|

Facile Iodine Detection via Fluorescence Quenching of β‐Cyclodextrin:Bimane‐Ditriazole Inclusion Complexes

Abstract: Reported herein is the detection of iodine using a non‐covalent association complex formed between a β‐cyclodextrin host and a designer bimane ditriazole guest. This complex responds to the presence of iodine with a marked decrease in the observed fluorescence signal. A sub‐nanomolar detection limit of this system in the solution‐state was determined. Moreover, results using filter paper onto which the β‐cyclodextrin‐bimane complex was adsorbed show a noticeable advantage compared to the cyclodextrin‐free bima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 41 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…Recent reports from one of our research groups have demonstrated the development of high-performance fluorometric ( Haynes and Levine 2020 ) and colorimetric ( Haynes et al, 2019 ) sensors for a variety of organic and inorganic analytes. Moreover, recent successes in novel sensor development have been reported in joint publications from our research groups, and demonstrate that bimane-based supramolecular constructs act as highly effective sensors for cobalt (II) ions ( Pramanik et al, 2020 ) and for molecular iodine ( Pramanik et al, 2021 ). These sensors, which operate in both solution-state and on filter papers to provide fluorometric and colorimetric analyte detection, have notable practical advantages, including their high sensitivity, ease of access, and non-toxicity of both the bimane transducing element and supramolecular cyclodextrin scaffold.…”
Section: Introductionmentioning
confidence: 93%
“…Recent reports from one of our research groups have demonstrated the development of high-performance fluorometric ( Haynes and Levine 2020 ) and colorimetric ( Haynes et al, 2019 ) sensors for a variety of organic and inorganic analytes. Moreover, recent successes in novel sensor development have been reported in joint publications from our research groups, and demonstrate that bimane-based supramolecular constructs act as highly effective sensors for cobalt (II) ions ( Pramanik et al, 2020 ) and for molecular iodine ( Pramanik et al, 2021 ). These sensors, which operate in both solution-state and on filter papers to provide fluorometric and colorimetric analyte detection, have notable practical advantages, including their high sensitivity, ease of access, and non-toxicity of both the bimane transducing element and supramolecular cyclodextrin scaffold.…”
Section: Introductionmentioning
confidence: 93%
“…In addition to the broadening of the triazole proton signals upon introduction of Cu(II), additional evidence in support of the interaction between Cu(II) and triazole was observed from two-dimensional HMBC experiments, which showed that the strong correlations between 15 N-1 H and between 13 C-1 H for the triazole moiety in 1 disappeared upon the addition of Cu(II). Of note, the chemical shift pattern of 1 H NMR spectrum of 1 does not change with the addition of increasing amounts of Cu(II), indicating that the symmetry of the complex must remain the same as the symmetry of the free bimane ligand.…”
mentioning
confidence: 90%
“…We have reported improved methods for the synthesis of bimane derivatives, 11 as well as the use of bimanes as sensors for cobalt(II) cations 12 and molecular iodine. 13 Despite the fact that bimane is known to bind a variety of metal ions in a way that modulates its fluorescence intensity, 14 we have not yet reported the use of a bimane-metal complex as a fluorescent sensor for other target analytes.…”
mentioning
confidence: 99%
“…These oligosaccharides made of 6 (α), 7 (β) or 8 (γ) glucopyranose units exhibit a hydrophobic internal cavity capable of hosting a large variety of inorganic compounds of appropriate size and shape [11]. These macrocyclic cavitands have found utility in various fields of application such as catalysis [12], materials science [13], sensing [14], and drug delivery [15]. Driven by the chaotropic effect, CDs can remarkably encapsulate either cationic [16], anionic [17][18][19][20] or even neutral metallic species [21].…”
Section: Introductionmentioning
confidence: 99%
“…Among the large family of POM structures, known examples of complexation with CD include Lindqvist [26], Keggin [23,27], and Dawson-type POMs [22]. In addition, inclusion complexes with the gigantic blue wheel [Mo 154 O 462 H 14 (H 2 O) 70 ] 14− have also been observed with role reversal where the cyclic POM acts as a CD-encapsulating host [28]. In this contribution, we report the synthesis, crystal structure, solution behavior and electrochemical properties of a new supramolecular adduct between γ-CD and another POM-type, namely the Preyssler anion [NaP 5 W 30 O 110 ] 14− .…”
Section: Introductionmentioning
confidence: 99%